Knowledge, attitude and practice regarding blood donation among medical students of Tamil Nadu- a cross sectional study - Govindasamy, Venkatesh; Sivasankaran, Devendiran; Purushothaman, Vaithiyanathan (International Journal Of Community Medicine And Public Health, 2019)
Background: Blood can save millions of life. Blood transfusion is one of the most crucial interventions in conditions like trauma, childbirth, and various other medical and surgical life-saving procedures. In spite of extensive efforts and a number of blood donation programs being organized worldwide, the availability of blood remains too short to meet the demand. Students of health education form a potential source of eligible regular voluntary donors and also play a cruel role in motivating potential donors from the general population. Methods: A cross sectional study was conducted among the medical students and interns of Government Thiruvannamalai Medical College in July 2018. Universal sampling was done for this study. A pretested structured questionnaire was used for data collection. Data entry and analysis was done using SPSS software version 21. Results: Out of 460 students, 53.3% have adequate knowledge about blood donation. 57.8% of students have positive attitude towards blood donation. Only 31.4% of them have donated blood before and anaemia was found to be the main reason among non-donors for not having donated blood. Conclusions: More than half of the students have adequate knowledge and positive attitude towards blood donation. Less than one-third have donated blood. It is recommended that there is a need to adopt strategies to sensitize and motivate them towards voluntary blood donation early in their medical career.